Holistic Approach in Risk and Security Management on Public Information - Yudie Aprianto (Pusjar SKPP Lembaga Administrasi Negara, 2021)
Public information is one of the government's efforts to provide public information regarding their performance and activities. However, even some regulations guide them, practice in public information management has not been optimal considering the information risks and threats, such as disclosing inappropriate information. For this reason, the literature study seeks to explore some efforts that can be made in information management, especially in Indonesia. This qualitative study tries to categorize and describe the management of public information in risk management and public information security in terms of technological management, process management, and human resource management. Technological management is expected to have an information system capable of providing a sense of security from threats, both malware and in building an effective system. Process management includes procedures, auditing, and a holistic approach to realizing effective public information management. Finally, human resource management emphasizes the importance of improving the quality of agents through training and leadership to act not only as a leader but also as a navigator and a translator of public information management. This study proposes a conceptual model based on those themes to minimize the effects of risks and threats on public information. Limitations and suggestions for future research are also discussed.